META ANALYSIS OF THE EFFECT OF CLASSROOM MANAGEMENT ON STUDENT LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Zahrotun Nafisah; Nafiah; Muhammad Thamrin Hidayat; Sri Hartatik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Classroom management is very important in the teaching and learning process with proper and appropriate classroom management, students will feel comfortable and happy when receiving learning materials so that learning outcomes are expected to be better with proper management; therefore, an educator is expected to master management class well. The purpose of this study was to analyze the effect of classroom management on student learning outcomes in elementary schools. The research method used was the type of meta-analysis research which data collection techniques carried out by using documentation techniques in the form of articles that are on Google Scholar. Data analysis technique used was to use comparative analysis. The results showed the influence of classroom management on student learning outcomes in elementary schools had a positive and significant effect with a percentage level of 77.8% of the results of the analyzed articles had a positive effect, while 22.2% of the results of the analyzed research stated that there was no effect because there were other factors that affected student learning outcomes not from classroom management by the teacher. The recommendations of this study are 1) teachers should master the proper classroom management, good and in accordance with students so that they can improve elementary student learning outcomes, 2) for other researchers, there should be further research related to the results of this study so that it can be used as a basis further research.